2014
DOI: 10.3390/ijerph110303407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Health Risks of Hand, Foot and Mouth Disease in China Using the Geographical Detector Technique

Abstract: Hand, foot and mouth disease (HFMD) is a common infectious disease, causing thousands of deaths among children in China over the past two decades. Environmental risk factors such as meteorological factors, population factors and economic factors may affect the incidence of HFMD. In the current paper, we used a novel model—geographical detector technique to analyze the effect of these factors on the incidence of HFMD in China. We collected HFMD cases from 2,309 counties during May 2008 in China. The monthly cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 27 publications
11
70
1
Order By: Relevance
“…More studies are still needed to explore if DED is a more prevalent condition among females, with a focus on different types of DED. In the exploration of geo-epidemiology of DED prevalence, increased latitude was found to be a risk factor for DED by symptoms and signs in our study, given that low relative humidity is a well-proven risk factor for DED [3,46], the negative relation of relative humidity and latitude in China may be the reason for this spatial distribution of DED by symptoms and signs [23,47,48]. The absence of a geographic variation of DED by symptoms may be due to the limited number of unique study sites, which was only 11.…”
Section: Discussionmentioning
confidence: 82%
“…More studies are still needed to explore if DED is a more prevalent condition among females, with a focus on different types of DED. In the exploration of geo-epidemiology of DED prevalence, increased latitude was found to be a risk factor for DED by symptoms and signs in our study, given that low relative humidity is a well-proven risk factor for DED [3,46], the negative relation of relative humidity and latitude in China may be the reason for this spatial distribution of DED by symptoms and signs [23,47,48]. The absence of a geographic variation of DED by symptoms may be due to the limited number of unique study sites, which was only 11.…”
Section: Discussionmentioning
confidence: 82%
“…The geographical detector proposed by Wang et al [30] is a novel and suitable spatial analysis method to detect the influential force on certain geographic and environmental phenomena, which has been applied in many fields in recent years [31,32,33]. We used factor detector, one module of the geographical detector, to determinate the impact of socioeconomic indicators on PMAE in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile the Thai National Disease Control Center reported that most of the HFMD outbreaks occurred in the day care center, and the risk factors were unregular hand washing of children and also limited knowledge on disease control and prevention among the caregivers in the day care center [21]. Huang et al also reported that economy and population density were risk factors of HFMD [22].…”
Section: Discussionmentioning
confidence: 99%